Recovery of the valuable metals from complex converter slag at elevated temperature with sulfuric acid solution - Liao Y.-L.; Shi G.-C.; Huang F.-R.; Zhang Y. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The aim of this paper was exploring the effective utilization of nickel converter slag by means of the methodology of pressure oxidative leaching. The central composite design of response surface methodology was employed to optimize controlling conditions for the leaching of more valuable metals such as nickel, cobalt, and copper, while dissolution of iron was curbed. XRD, SEM-EDS were performed for characterizing the structure of leach residues for analyzing the mechanism of selective leaching. Experimental results demonstrate that the effects of temperature and sulfuric acid concentration on the metals extraction and filtration rate are significant, followed by liquid/solid (L/S) ratio. The optimized conditions for the leaching of converter slag are: temperature 208 °C, sulfuric acid concentration 0.35 mol/L, and L/S ratio 5.4 mL/g. Under these conditions, 99.60% Co, 99.20% Ni, and 96.80% Cu were extracted into solution together with only 0.21% Fe, and the filtration rate of leach slurry reached 576.86 L∙m‒2∙h‒1. The mechanism for achieving selective leaching of nickel, cobalt, and copper against iron dissolution and good filtration performance of the leach slurry was enabled by iron that dissolved in the solution, decomposed, and hydrolyzed mainly to form hematite (α-Fe2O3 and γ-Fe2O3), and letting silicic acid form precipitated SiO2 in the leach residue.